Development of Flip Book Maker Learning Media on Asymmetrical Styling Patterns for Bun and Hair Styling Course for Cosmetology Education Students, Universitas Negeri Medan - Mei Alsih Sihombing; Dian Maya Sari; Rossy Luckita Sasmita; Farida Hasanah Lumban Gaol (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to determine the development of flipbook maker products as a learning media for asymmetrical pattern hairstyling and to determine the feasibility of flipbook maker as a learning media for asymmetrical pattern hairstyling. In this study the method used is research and development method (Research & Development), which is a research method that aims to develop and test a product that will be produced for learning activities. The data collection technique was done through a questionnaire. While the data analysis technique used is quantitative. The validation test was carried out by media experts and material experts consisting of three lecturers from the Faculty of Engineering, State University of Medan who are competent in hairdressing lessons. While media experts are three lecturers from the Faculty of Engineering, State University of Medan. The results showed that the product developed in the form of media flipbook maker teaching material for asymmetrical pattern hair styling based on the assessment of the material experts obtained a score of 92.2%, meaning that the material contained in the flipbook maker was declared very good. While the assessment of media experts, the product developed in the form of a flipbook maker on asymmetrical pattern hair styling material obtained a score of 93.2%, meaning that the media display contained in the flipbook maker was declared very good. Based on the results of the media product trials conducted on three groups, it can be seen that based on the calculation in the small group trial the overall results reached 87.3%, in the medium group trial the overall results reached 93.4%. Likewise, the calculation in the large group trial reached 94%, with an average overall score of 91.5%. It can be concluded that the media flipbook maker asymmetrical pattern hair styling material is declared feasible for use in learning activities by educators and students.